Cognitive effects of repetitive transcranial magnetic stimulation in patients with neurodegenerative diseases - clinician's perspective - Anderkova, Lubomira; Rektorova, Irena (Journal of the neurological sciences, 2014)
Repetitive transcranial magnetic stimulation (rTMS) represents a promising tool for studying and influencing cognition in people with neurodegenerative diseases. This procedure is noninvasive and painless, and it does not require the use of anesthesia or pharmacological substances. In this systematic critical review we report outcomes from research focused on behavioral cognitive effects induced by rTMS in patients with Alzheimer's disease (AD), Parkinson's disease (PD), and mild cognitive impairment (MCI) preceding AD. There are still major limitations to rTMS use, such as a poor understanding of its after-effects and inter-individual variability in their magnitude, discrepancies in stimulation protocols and study designs, varied selection of the specific stimulated areas and control procedures, and neuropsychological methods for assessment of after-effects; hence, the results of the present research can only be considered preliminary. The future directions are discussed.
Keywords: zvířata; Neurodegenerative Diseases; Transcranial Magnetic Stimulation; Cognitive Dysfunction; kognitivní dysfunkce; Physician's Role; neurodegenerativní nemoci; Neurodegenerative; Alzheimer's disease; Animals; Alzheimer Disease; kognice; Parkinson's disease; Systematic review; transkraniální magnetická stimulace; role lékaře; Parkinson Disease; Cognition; Parkinsonova nemoc; lidé; Humans; MCI; rTMS; Alzheimerova nemoc